2019
DOI: 10.3389/fmicb.2019.01587
|View full text |Cite
|
Sign up to set email alerts
|

Biological Synthesis of CdS/CdSe Core/Shell Nanoparticles and Its Application in Quantum Dot Sensitized Solar Cells

Abstract: In the present work, we report the use of bacterial cells for the production of CdS/CdSe Core/Shell quantum dots (QDs), a complex nanostructure specially designed to improve their performance as photosensitizer in photovoltaic devices. The method requires the incorporation of L-cysteine, CdCl 2 and Na 2 SeO 3 to Escherichia coli cultures and allows a tight control of QDs properties. The obtained CdS/CdSe QDs were photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…This is puzzling considering the fluorescent and structural properties determined for these QDs. Previous works in biosynthesized CdS QDs with similar properties to those described here (size, composition, QY, and emission), reported XRD results indicating the existence of crystalline structures [ 8 , 36 , 37 , 56 ]. This result is most probably a consequence of the amorphous matrix of organic matter that covers the QDs produced by Pedobacter sp.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is puzzling considering the fluorescent and structural properties determined for these QDs. Previous works in biosynthesized CdS QDs with similar properties to those described here (size, composition, QY, and emission), reported XRD results indicating the existence of crystalline structures [ 8 , 36 , 37 , 56 ]. This result is most probably a consequence of the amorphous matrix of organic matter that covers the QDs produced by Pedobacter sp.…”
Section: Discussionsupporting
confidence: 76%
“…Regarding the application of biosynthesized QDs as photosensitizer materials in the construction of solar cells, as far as we can tell, there had been only a few previous works. In Spangler et al [ 57 ], an engineered strain of Stenotrophomonas maltophilia was used to produce PbS NPs, while in the works Órdenes-Aenishanslins et al [ 56 , 58 ], the bacteria employed was an Escherichia coli strain that was able to synthesize CdS QDs. To date, Pedobacter genus has not been used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This biosynthetic process is highly versatile and has been recently used for the controlled production of CdS/CdSe Core/Shell QDs. These Cd-based nanomaterials were specifically designed for photovoltaic applications and their use as "bio-sensitizers" in QDs-sensitized solar cells was reported for the first time [22]. Based on this and the inherent advantages of using microorganisms as nanocrystal bio-factories, we believe that the biosynthesis process constitutes a unique opportunity to generate nanoparticles with improved properties, such as ternary QDs, that could contribute to the development of new technologies and applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution, investigators have found that the heterogeneous, composite semiconductors have superior optical optoelectronic and physical properties as compared to the single material [12]. In recent years, a single semiconductor material coated with another material (known as core/shell nanostructure) has also gained prominence [13][14][15][16][17][18]. The shell materials are coated for controlling the reactivity and stability of the core [19].…”
Section: Introductionmentioning
confidence: 99%